2022
DOI: 10.1101/2022.11.21.517369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bioresorbable Mesenchymal Stem Cell–Loaded Electrospun Polymeric Scaffold Inhibits Neointimal Hyperplasia Following Arteriovenous Fistula Formation in a Rat Model of Chronic Kidney Disease

Abstract: In the setting of chronic kidney disease (CKD), the periadventitial injection of mesenchymal stem cells (MSCs) has shown significant potential in improving arteriovenous fistula (AVF) maturation by inhibiting neointimal hyperplasia (NIH). However, the rapid clearance of MSCs remains a challenge. Hence, we fabricated an electrospun perivascular scaffold from polycaprolactone (PCL) to support MSC attachment and allow gradual MSC elution at the outflow vein, the AVF site most prone to NIH. We performed 5/6th neph… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(74 reference statements)
2
5
0
Order By: Relevance
“…We found that PCL+MSC and PCL-Au+MSC AVFs demonstrated an improved wall-to- lumen ratio, a marker of vascular stenosis, compared with AVFs without MSCs in as early as 2 weeks after AVF creation. This is consistent with the results of a prior study, wherein the addition of MSCs to polymeric wrap reduced the AVF wall-to-lumen ratio when compared to polymeric wrap alone at 4 weeks after AVF creation (10). These results highlight the unique role of MSCs in improving AVF maturation.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that PCL+MSC and PCL-Au+MSC AVFs demonstrated an improved wall-to- lumen ratio, a marker of vascular stenosis, compared with AVFs without MSCs in as early as 2 weeks after AVF creation. This is consistent with the results of a prior study, wherein the addition of MSCs to polymeric wrap reduced the AVF wall-to-lumen ratio when compared to polymeric wrap alone at 4 weeks after AVF creation (10). These results highlight the unique role of MSCs in improving AVF maturation.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that all treatment groups demonstrated improved neointima-to-lumen ratios, a measure of NIH, versus control rats by 8 weeks after AVF creation. Our findings show that the reduction in the neointima-to-lumen ratio by PCL and PCL+MSC treatment versus control seen at 4 weeks after AVF creation in a previous study (10) can be maintained for up to 8 weeks. Moreover, the incorporation of AuNPs did not affect the ability of the wraps to reduce the AVF neointima-to-lumen ratio.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations